PENGARUH PERMAINAN TRADISIONAL BAKIAK TERHADAP PERKEMBANGAN MOTORIK KASAR ANAK DI TK KEMALA BHAYANGKARI PALU - Amrullah, Amrullah; Sita Awalunisah (Jurnal Golden Age, 2025)
Gross motor skills for early childhood are very important to be stimulated because they greatly support the child's life in the future. The development of children's gross motor skills is a movement that uses large muscles owned by children to carry out their activities or activities, one of the games to develop children's large muscles is by using clog games. The purpose of this study was to see the effect of clog games on the development of gross motor skills in children aged 5-6 years. The study used a quantitative descriptive approach and used a one group design approach. The research sample consisted of 14 children. Data collection used observation and documentation techniques. Based on the results of initial observations and final observations, a significant increase was found in children's gross motor skills with aspects of speed, smoothness and flexibility of early childhood children. This means that traditional clog games have an effect on the development of children's gross motor skills. This can be seen in the results of the t-test with a significant value of 0.00 <0.05 in accordance with the basis of decision-making ability in paired sample tests, it can be concluded that traditional clog games have a significant effect on the development of children's gross motor skills.